2022
DOI: 10.3390/brainsci12070845
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to Social-Linguistic Associations in Audio-Visual Speech

Abstract: Listeners entertain hypotheses about how social characteristics affect a speaker’s pronunciation. While some of these hypotheses may be representative of a demographic, thus facilitating spoken language processing, others may be erroneous stereotypes that impede comprehension. As a case in point, listeners’ stereotypes of language and ethnicity pairings in varieties of North American English can improve intelligibility and comprehension, or hinder these processes. Using audio-visual speech this study examines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…By informing subjects in the experiment that the speakers were from Richmond (i.e., a suburb known for its Cantonese-speaking community), the authors may have strengthened their social priming manipulation. Further investigation within this community of listeners using audiovisual stimuli has also demonstrated that adaptation to L2 accent is impeded when the speaker is White (Babel, 2022), indicating that listeners anticipated the speaker to have L1 accent. In contrast, listeners were not impeded when listening to L1 accent produced by an Asian speaker.…”
Section: Discussionmentioning
confidence: 99%
“…By informing subjects in the experiment that the speakers were from Richmond (i.e., a suburb known for its Cantonese-speaking community), the authors may have strengthened their social priming manipulation. Further investigation within this community of listeners using audiovisual stimuli has also demonstrated that adaptation to L2 accent is impeded when the speaker is White (Babel, 2022), indicating that listeners anticipated the speaker to have L1 accent. In contrast, listeners were not impeded when listening to L1 accent produced by an Asian speaker.…”
Section: Discussionmentioning
confidence: 99%